Pengaruh Good Corporate Governance terhadap Integritas Laporan Keuangan (Perusahaan BUMN yang terdaftar di BEI Periode 2016-2020) - Khoirul Fahmi; Alvin Jeremiah (Sekolah Pascasarjana Perbanas Jakarta, 2023)
The main objective of this study is to examine whether GCG (Good Corporate Governance) consists of: managerial ownership, institutional ownership, audit committee, and independent commissioners. The research method is quantitative and the population in this study are state-owned companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period..The sample in this study used a purposive sampling method and obtained 14 companies that matched the criteria from 16 available companies with a study period of 5 years. The results of this study indicate that: (1) managerial ownership has no effect on the integrity of financial statements, (2) institutional ownership, and the audit committee has no effect on the integrity of financial statements, (3) the audit committee has no effect on the integrity of financial statements, (4) independent commissioners affect the integrity of financial statements, (5) Simultaneously the variables of managerial ownership, institutional ownership, audit committee, and independent commissioners simultaneously affect the integrity of financial statements.